1995
DOI: 10.1007/bf02191809
|View full text |Cite
|
Sign up to set email alerts
|

Clinical symptoms and regional cerebral blood flow in schizophrenia

Abstract: This study examined the relationship between clinical symptoms and regional cerebral blood flow (rCBF) in schizophrenic patients using single photon emission computed tomography (SPECT). The subjects were 26 medicated schizophrenic patients diagnosed according to DSM-III-R criteria. Clinical symptoms were assessed using the Scale for the Assessment of Negative Symptoms (SANS), selected items for the Positive and Negative Syndrome Scale (PANSS), and the scale for Schneider's first rank symptoms. Resting rCBF wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…For example, Ebmeier et al (1993), and Yuasa et al (1995) both confirmed that disorganization is associated with overactivity in anterior cingulate, though neither of these studies found an association with underactivity in the ventral frontal cortex.…”
Section: The Disorganization Syndrome In Schizophreniamentioning
confidence: 87%
See 1 more Smart Citation
“…For example, Ebmeier et al (1993), and Yuasa et al (1995) both confirmed that disorganization is associated with overactivity in anterior cingulate, though neither of these studies found an association with underactivity in the ventral frontal cortex.…”
Section: The Disorganization Syndrome In Schizophreniamentioning
confidence: 87%
“…There is a rather large body of evidence demonstrating that the anterior cingulate and lateral frontal cortex are abnormal in schizophrenia (Liddle et al 1992;Yuasa et al 1995) and growing evidence of such abnormalities in psychopathy (Kiehl et al 1999b). Given that response inhibition is most probably a function of a complex neural circuit located in a spatially distributed network, it may be possible that the topographic ERP differences observed between the patient groups may reflect abnormalities at one or more cerebral sites.…”
Section: Discussionmentioning
confidence: 99%
“…Associations with specific prefrontal areas, i.e., the dorsolateral prefrontal cortex (DLPFC) and the ventral prefrontal region, as well as other brain areas, in particular temporal and parietal regions, were also reported [65][66][67]. However, some studies failed to confirm these relationships [63,68], while others reported associations of negative symptoms with increased metabolism in the left frontal region [69], left thalamus and right basal ganglia [70] and temporal regions [67,71].…”
Section: Functional Neuroimaging Findingsmentioning
confidence: 90%
“…Functional imaging studies seeking regional associations between brain metabolism and negative symptoms have been typically based on correlation (Wolkin et al, 1992;Sabri et al, 1997), factor analysis Kaplan et al, 1993;Yuasa et al, 1995;Kawasaki et al, 1996;Schroder et al, 1996) or categorical (ie deficit vs nondeficit schizophrenia) (Andreasen et al, 1992;Heckers et al, 1999;Lahti et al, 2001;Potkin et al, 2002;Tamminga et al, 1992) analyses. The majority of these studies have reported hypometabolism in frontal cortex during rest Wolkin et al, 1992;Kaplan et al, 1993;Yuasa et al, 1995;Sabri et al, 1997) and task-activated states (Andreasen et al, 1992;Schroder et al, 1996;Potkin et al, 2002) in association with negative symptoms. In addition, three of these studies also showed reduced functional recruitment of the inferior parietal cortex in deficit compared to nondeficit subjects either at rest (Tamminga et al, 1992) or during task performance Heckers et al, 1999).…”
Section: Hippocampal/parahippocampal Regions: Normal Function and Abnmentioning
confidence: 99%